2012
DOI: 10.1016/j.expneurol.2011.12.037
|View full text |Cite
|
Sign up to set email alerts
|

Conditioning lesions before or after spinal cord injury recruit broad genetic mechanisms that sustain axonal regeneration: Superiority to camp-mediated effects

Abstract: Previous studies indicate that peripheral nerve conditioning lesions significantly enhance central axonal regeneration via modulation of cAMP-mediated mechanisms. To gain insight into the nature and temporal dependence of neural mechanisms underlying conditioning lesion effects on central axonal regeneration, we compared the efficacy of peripheral sciatic nerve crush lesions to cAMP elevations (in lumbar dorsal root ganglia) on central sensory axonal regeneration when administered either before or after cervic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
90
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 104 publications
(98 citation statements)
references
References 55 publications
4
90
0
Order By: Relevance
“…Outgrowth-Double labeling for LRP1 and NF200, a marker for large-diameter neurons (30), demonstrated that LRP1 is expressed by intact adult, large-diameter DRG neurons and some smaller DRG neurons (Fig. 1A).…”
Section: Lrp1 Is Expressed In Adult Drg Neurons and Lrp1 Activation mentioning
confidence: 99%
See 1 more Smart Citation
“…Outgrowth-Double labeling for LRP1 and NF200, a marker for large-diameter neurons (30), demonstrated that LRP1 is expressed by intact adult, large-diameter DRG neurons and some smaller DRG neurons (Fig. 1A).…”
Section: Lrp1 Is Expressed In Adult Drg Neurons and Lrp1 Activation mentioning
confidence: 99%
“…In Vitro Studies-Primary cultures of adult F344 L4-L6 DRG neurons were cultured on poly-L-lysine-coated (16.6 g/ml) 12-well plates as described previously (30). Cells were treated with 100 nM RBD, PEX, or GST for 18 or 24 h. In some assays, cells were pretreated with GST-RAP (200 nM) 30 min prior to the addition of LRP1 agonists.…”
Section: Neurite Outgrowth In Cultures Of Adult Drg Neuronsmentioning
confidence: 99%
“…In the conditioning lesion paradigm, lesion of the peripheral, but not central DRG axon induces a cascade of signaling events in the axon and neuronal soma that enhances the intrinsic growth state of the neuron (140). Notably, this conditioning lesion also enhances regeneration of the injured central axon branch if performed prior to, or shortly after the central lesion (64,141).…”
Section: Importance Of Proteomics In Identifying Mechanismsmentioning
confidence: 99%
“…Injured DRG neurons rapidly activate a transcriptional program of hundreds of genes as early as 1 day postinjury, and the majority of these exhibit sustained expression patterns by 2 weeks postinjury (141, 142) (140,141,(143)(144)(145)(146)(147)(148)(149). Because this gene expression program is not activated upon central axotomy, many groups have endeavored to promote CNS axon regeneration via the exogenous expression of regeneration associated genes or their upstream regulators (2,150).…”
Section: Importance Of Proteomics In Identifying Mechanismsmentioning
confidence: 99%
“…This study also highlighted that the delivery of 1 growth factor to the CNS may augment the production of other growth factors, thereby sustaining neuronal growth or survival. In another study, continuous infusion of NT-3 into the dorsal spinal cord was reported to promote the growth of sensory axons from a peripheral nerve graft into the dorsal column white matter (Blesch et al, 2012). A variety of axonal populations of the spinal cord respond to neurotrophic factors (Brock et al, 2010).…”
Section: Discussionmentioning
confidence: 99%